Optimización de presión en cámaras de flujo para reducir riesgo de fugas en el estudio de Trypanosoma cruzi (2025)
Chagas disease is a chronic, incurable condition that primarily affects Latin America and continues to represent a significant public health challenge, particularly in rural areas where the parasite’s hosts reside. Studying the adhesion mechanisms of Trypanosoma cruzi offers the potential to develop new therapies. The analysis of tripomastigotes in human cells is conducted in flow chambers or PDMS chips, with the aim of understanding the mechanisms the parasite uses to adhere to cells under flow conditions. However, this study carries a risk due to spills that occur in the flow chambers, caused by the pressure difference between the inside of the channel and the external atmospheric pressure. To address this issue, a theoretical model was developed to optimize the pressure difference between the chamber and the atmosphere, adjusting parameters such as the height of the hoses used in the experiment. The use of this model allowed the determination of optimal hose heights that minimize the pressure difference between the inside of the channel and the atmospheric pressure, thereby reducing the experimental risk.